2022
DOI: 10.1021/acsanm.2c03303
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Excitation Intensity-Dependent Fluorescence Intensity Ratio of Upconversion Nanoparticles on Wide-Field Thermal Imaging

Abstract: Erbium ion (Er 3+ )-doped upconversion nanoparticles (UCNPs) are frequently used for nanothermometry because their fluorescence intensity ratio (FIR) between two green emission bands at ∼525 and ∼545 nm is sensitive to temperature variation. One of the prerequisites for nanothermometry is that the FIR be independent of excitation intensity at constant temperature. In this work, the effect of excitation intensity on the FIR of core−double-shell NaYF 4 :Yb 3+ ,Er 3+ @NaYF 4 :Yb 3+ ,Nd 3+ @NaYF 4 UCNPs was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Complementary rate equation modeling instead showed that a combination of radiative and nonradiative relaxation from higher-lying Er 3+ energy levels that become heavily populated at high single-particle excitation intensities increases the temperature-dependent ratio. Working in a lower excitation intensity range, Nguyen et al instead identified a decrease in the ratio with excitation intensity that was attributed to decreased population of the 2 H 11/2 excited state. Several works have identified emission from the 2 H 9/2 to 4 I 13/2 transition of Er 3+ , which is frequently observed at higher excitation intensities and overlaps spectrally with the 4 S 3/2 to 4 I 15/2 Er 3+ transition used for ratiometric thermometry, as a source of measurement artifacts. , Because the 2 H 9/2 to 4 I 13/2 transition results from a three-photon upconversion process, the emission from this transition displays a different excitation intensity scaling than the Er 3+ transitions used for ratiometric thermometry that originate from two-photon upconversion processes, leading to errors in temperature measurements where the excitation intensity is varied (Figure d).…”
Section: Emerging Areasmentioning
confidence: 99%
See 2 more Smart Citations
“…Complementary rate equation modeling instead showed that a combination of radiative and nonradiative relaxation from higher-lying Er 3+ energy levels that become heavily populated at high single-particle excitation intensities increases the temperature-dependent ratio. Working in a lower excitation intensity range, Nguyen et al instead identified a decrease in the ratio with excitation intensity that was attributed to decreased population of the 2 H 11/2 excited state. Several works have identified emission from the 2 H 9/2 to 4 I 13/2 transition of Er 3+ , which is frequently observed at higher excitation intensities and overlaps spectrally with the 4 S 3/2 to 4 I 15/2 Er 3+ transition used for ratiometric thermometry, as a source of measurement artifacts. , Because the 2 H 9/2 to 4 I 13/2 transition results from a three-photon upconversion process, the emission from this transition displays a different excitation intensity scaling than the Er 3+ transitions used for ratiometric thermometry that originate from two-photon upconversion processes, leading to errors in temperature measurements where the excitation intensity is varied (Figure d).…”
Section: Emerging Areasmentioning
confidence: 99%
“…Some excitation intensity-dependent artifacts can be avoided or mitigated by working at fixed or low excitation intensities. Another approach is to correct the ratio by subtracting or dividing out an excitation intensity-dependent term. , Martins et al also demonstrated the disappearance of the emission from the 2 H 9/2 to 4 I 13/2 transition when the excitation wavelength was switched from 980 to 808 nm. Alternatively, deconvolution or experimental procedures , can be applied to separate and subsequently remove the emission originating from the 2 H 9/2 to 4 I 13/2 transition prior to calculating the ratio.…”
Section: Emerging Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…UCNPs typically consist of a crystalline host, such as sodium yttrium tetrafluoride (NaYF 4 ), codoped with trivalent lanthanide ion sensitizers (ytterbium, Yb 3+ , and neodymium, Nd 3+ ) and activators (erbium, Er 3+ , thulium, Tm 3+ , and holmium, Ho 3+ ). UCNPs have excellent photophysical properties, such as narrow emission lines, high photostability, no photobleaching, no autofluorescence, and low background signal. …”
mentioning
confidence: 99%